Do accounting standards affect PMS tools? The case of IAS/IFRS adoption in Italy. (1st January 2011) - Guerrini, Andrea; Cantele, Silvia; Modina, Silvio; Campedelli, Bettina
The objective of this project was to investigate the impact of the adoption of international accounting standards (IAS/IFRS) on a company's performance measurement system (PMS). This study was conducted through a questionnaire sent to Italian companies that drafted a financial statement adopting the new accounting standards. Our analysis showed that in most cases the companies made only gradual upgrades and changes to their PMS, limiting the introduction of new accounting tools to manage the switchover to IAS/IFRS standards. At the same time, there was little impact on company organisation and the span of control of the PMS caused by the shift to IAS/IFRS.